2011
DOI: 10.1007/s10658-011-9820-4
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive potential of the root-knot nematode Meloidogyne incognita is affected by selection for virulence against major resistance genes from tomato and pepper

Abstract: The emergence of virulent root-knot nematode populations, able to overcome the resistance conferred by some of the resistance genes (R-genes) in Solanaceous crops, i.e., Mi(s) in tomato, Me(s) in pepper, may constitute a severe limitation to their use in the field. Research has been conducted to evaluate the durability of these R-genes, by comparing the reproduction of several laboratory-selected and wild virulent Meloidogyne incognita isolates, on both susceptible and resistant tomatoes and peppers. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 34 publications
12
76
0
4
Order By: Relevance
“…Moreover, the response of the pepper cultivars carrying the gene Me3 seemed to depend on the Meloidogyne population. This was confirmed with several laboratory-selected and natural M. incognita virulent isolates (Djian-Caporalino et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, the response of the pepper cultivars carrying the gene Me3 seemed to depend on the Meloidogyne population. This was confirmed with several laboratory-selected and natural M. incognita virulent isolates (Djian-Caporalino et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…Previous work by Castagnone-Sereno et al (2001) and Djian-Caporalino et al (2011) demonstrated that selection of virulence was highly specific, as naturally occurring and laboratory selected Mi-virulent nematodes to resistant tomato were unable to multiply on resistant peppers carrying the Me3 (= Me7) resistance gene and viceversa. The Me1 gene showed itself to be robust, as none of the virulent populations against Mi, and Me3 (= Me7) multiplied on peppers containing the Me1 resistance gene.…”
Section: Development Of Virulence Tomentioning
confidence: 99%
“…The durability of resistance mostly depends upon the occurrence of virulence isolates of nematode. Djian-Caporalino et al (2011) reported that a propagative fitness cost is linked to nematode virulence against Mi-1 in tomato. Although the resistance is broken down, it may be conserved in some conditions if the virulent nematodes are counter-selected in susceptible plants (Djian-Caporalino et al 2011).…”
Section: Natural Resistance Gene In Controlling Rknmentioning
confidence: 99%
“…Djian-Caporalino et al (2011) reported that a propagative fitness cost is linked to nematode virulence against Mi-1 in tomato. Although the resistance is broken down, it may be conserved in some conditions if the virulent nematodes are counter-selected in susceptible plants (Djian-Caporalino et al 2011). Therefore, the durability should be assessed either by long-term cropping of resistant cultivars or by cultivating resistant cultivars under high inoculum pressure.…”
Section: Natural Resistance Gene In Controlling Rknmentioning
confidence: 99%
“…Many studies showed that root knot nematode species (RKNs), which causes a major economic loss throughout the world, have very broad host ranges. Some other species of nematode are limited to one or a few hosts (Djian-Caporalino et al, 2011;Gleason et al, 2008). For example, cyst nematodes usually have narrower host ranges.…”
Section: Introductionmentioning
confidence: 99%